TEACHING MATERIALS OF ENGLISH FOR STUDENTS OF MECHANICAL ENGINEERING OF ENGINEERING FACULTY DARMA AGUNG UNIVERSITY MEDAN- A NEED ANALYSIS ON ESP PERSPECTIVE - Corry Ester Margaret Siagian (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2018)
Teaching materials that meet the students need must be gained from deep analysis of student’s needs that can involve not only the students but also lecturer, staff workers from students’ preferred workplace. It should cover the topics needed, relevant tasks, answering the students’ lacks, and touch the most priority of English language skill needed. Need analysis found is needed to design content and aims of the course which are oriented to the specific needs of the learners. This research revealed that The background of English of the students are not good and the students learned the general English not mostly specific for the Mechanical engineering students; connecting word to word or sentence to sentence (33%), vocabularies (21%), grammar (22%), Pronunciation (9%), Finding the main topic (9%), and others (6%) are their most difficulties ; The Genre Based Vocabularies and topics of the teaching materials which are suitable are as follows: The Core of Greetings, The Core of Introducing Oneself, the core of Company Profile and workplace, The Core of Reporting or Making Report, The Core of Giving and Asking Information, The Core of Asking and Giving Direction, The Core of Statistics, The Core of Interview, The Core of Job Application, The Core of Delivering a Presentation, The Core of Writing Letters, The Core of Explaining Process, The Core of Telephone Calls. It is also revealed that the students are needed to be taught in a learning atmosphere that encourages them to be more active in learning in the classroom with their low competencies and low motivation and still need the lecturer explanation and help at first followed by learning English in autonomous way. Teaching materials mechanical engineering need analysis ESP.